Consolidação e perspectivas da agroindústria paranaense ante o mercado externo - Pereira, Laércio Barbosa (Estudos Econômicos (São Paulo), 1996)
It analyses the participation ofParanáState’s and Brazilian exports in the international market during the last two decades. They underwent significant changes due to both a diversification process into tradable goods with an increase in the export of capital intensive goods, and a diversification of the market for these goods. However, the performance of Paraná State’s exports were far below the world and the Brazilian export performance. The principal causes were: first, although it has occured a change in the export profile towards industrial goods exports, these were still mainly from agricultural origin; second, during the 80s, the dinamism of world exports was determined by industrial goods; third, exports were concentrated on EEC countries, around 50%. Fourth, there was an increase in the protecionism from developed countries against the agricultural imports, imposed mainly by the EEC countries. Besides, the prospects for the increase inParanáState’s agroindustrial exports are rather unfavourable due to the emergence of regional blocks, the new protecionism, the increase in the international competition, the high level of subsidies, and the market saturation for agroindustrial goods.